1997
DOI: 10.1103/physrevlett.78.2968
|View full text |Cite
|
Sign up to set email alerts
|

Microfilamentation in Optical-Field-Induced Ionization Process

Abstract: A plasma-resonance field-ionization instability of uniform gas breakdown produced by intense laser fields via tunneling ionization of atoms is studied theoretically and by computer simulation. The field amplitude and produced plasma are found to be unstable relative to spatial modulation in the direction of electric field with the spatial period shorter than the wavelength. In a dense gas the process, at the nonlinear stage of instability, becomes explosive and leads to the formation of thin resonance layers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
(9 reference statements)
0
20
0
Order By: Relevance
“…With the terawatt lasers now being used in a wide range of plasma experiments this intensity threshold can be achieved well before the beam reaches its focus. This ionization process leads to a number of interesting nonlinear phenomena, including frequency upshifting of the laser radiation by the moving ionization front [1-7], refractive defocusing of the laser pulse due to the radial inhomogeneity of the plasma electron density [8,9], and harmonic generation due to the nonlinear dependence of the ionization rate on the field amplitude [8].An additional effect that has received only a small amount of attention is the possible scattering of the radiation by the collective amplification of modulations of the electron density transverse to the initial direction of propagation of the laser pulse [10][11][12]. Such a transversely modulated density appears in the presence of transverse modulations of the laser amplitude due to the dependence of the ionization rate on field amplitude.…”
mentioning
confidence: 99%
“…With the terawatt lasers now being used in a wide range of plasma experiments this intensity threshold can be achieved well before the beam reaches its focus. This ionization process leads to a number of interesting nonlinear phenomena, including frequency upshifting of the laser radiation by the moving ionization front [1-7], refractive defocusing of the laser pulse due to the radial inhomogeneity of the plasma electron density [8,9], and harmonic generation due to the nonlinear dependence of the ionization rate on the field amplitude [8].An additional effect that has received only a small amount of attention is the possible scattering of the radiation by the collective amplification of modulations of the electron density transverse to the initial direction of propagation of the laser pulse [10][11][12]. Such a transversely modulated density appears in the presence of transverse modulations of the laser amplitude due to the dependence of the ionization rate on field amplitude.…”
mentioning
confidence: 99%
“…The situation changes dramatically for high density gas, when plasma density approaches N cr . The transversal field in plasma inhomogeneities rapidly increases due to plasma resonance, 15 in turn leading to enhanced ionization, so, in fact, overdense plasma inhomogeneities for the TM polarization develop much faster than for the TE case ( Fig. 6(second row)), they are better localized in space and have sharper boundaries (Fig.…”
Section: Ionization Dynamics Of Tightly Focused Laser Pulsementioning
confidence: 95%
“…(20) may be high enough, it may still be insufficient in systems with small interaction volume (i.e., characteristic spatial scales are comparable with laser wavelength) for the instability to be well developed because of the convectional nature of the ionization scattering instability. 1 We also have to consider the spatial growth rate within dispersion equation (15) assuming γ = iΩ and the wavenumber κ to be a function of real Ω (frequency shift of the scattered waves). Since the inequality ωΩ kc 2 κ cos θ is readily satisfied in a broad range of parameters, except the case of forward scattering with large-scale density perturbations, solution of Eq.…”
Section: Dispersion Relationmentioning
confidence: 99%
“…In this context, Leemans et al 27 have shown that the tunnel ionization rate is exceptionally dependent on the laser field, which leads to steep plasma density gradients in the transverse or radial direction. Moreover, in the process of optical-field induced ionization, Gil'denburg et al 29 have reported that the field and plasma cannot stay homogeneous even on the small scales compared with the wavelength. In view of all these facts, it is necessary to consider the inhomogeneity in the plasma density in order to understand the more realistic situation.…”
Section: Frequency Of Oscillationsmentioning
confidence: 99%